(untitled) (Czech Journal of International Relations, 2002)
In this paper the author outlines an answer to the question of how and whether the results of the September parliamentary elections could affect Slovakia’s invitation to join NATO and its acceptance into the European Union (EU). The decisions of the North Atlantic Alliance summit to take place in the Czech capital in November 2002 and the European Council assembly at the end of the Danish presidency could have historic significance for the Slovak Republic. Favorable decisions at these gatherings could confirm that it is an integral part of the Central European region, not merely in terms of geography, but also with respect to its common values. Negative decisions could significantly prolong or seriously complicate its path to the ranks of the prosperous countries of the democratic world. Since its inception, all of the SR’s administrations have declared their ambitions to gain membership in both of the above mentioned institutions. However, not until the government of M. Džurinda did any Slovak administration tackle the necessary complex of procedures to truly bring the SR closer to its stated goals. The author offers his thoughts on the reasons why, in comparison to its neighbors, it has been more difficult for Slovakia to launch these integration processes and on the particular features of its domestic political scene. With a description of the economic and social situation, the author will search for explanations for the high levels of discontent among the citizens with the political direction of the country and the low approval ratings for the parties in the ruling coalition, despite the fact that they achieved extraordinary results in strengthening the international position of Slovakia. The author concludes that the most significant factor in its political situation less than a year before the regular parliamentary elections has to be the fact that Slovakia has become one of the most promising candidates for the next wave of EU expansion and one of the best prepared applicants for membership in the North Atlantic Alliance. This is clearly the greatest success that Slovakia has achieved, not just during the last election cycle, but ever since it became an independent state. On top of this, the positive changes in Slovakia’s internal political development are also often forgotten. Without these improvements, especially in the growth of democratic principles and the construction of a pluralistic society, the international position of Slovakia would never have gotten so much stronger. The answer to the most frequently asked question concerning Slovakia’s future, whether they will successfully wrap up their negotiations for EU accession and complete their preparations for membership in NATO, largely depends upon the results of September’s parliamentary elections. If it does not manage to form a sufficiently trustworthy government, which could provide a reliable guarantee of political continuity with the present administration, it is very likely that Slovakia will not receive an invitation to join NATO. Many politicians predict that in such a case the SR’s path to EU accession would be seriously complicated as well. However, the further international isolation of Slovakia would not just signify a major loss for its political elite, but would have serious negative consequences for the whole Central European region as well.